BAFF receptor antibody for mantle cell lymphoma therapy. (1st January 2021) - Zhang, Keman; Roy, Nand K; Vicioso, Yorleny; Woo, Janghee; Beck, Rose; de Lima, Marcos; Caimi, Paolo; Feinberg, Daniel; Parameswaran, Reshmi
ABSTRACT: Mantle cell lymphoma (MCL) is an aggressive form of B cell non-Hodgkin's lymphoma and remains incurable under current treatment modalities. One of the main reasons for treatment failure is the development of drug resistance. Accumulating evidence suggests that B cell activating factor (BAFF) and BAFF receptor (BAFF-R) play an important role in the proliferation and survival of malignant B cells. High serum BAFF levels are often correlated with poor drug response and relapse in MCL patients. Our study shows that BAFF-R is expressed on both MCL patient cells and cell lines. BAFF-R knockdown leads to MCL cell death showing the importance of BAFF-R signaling in MCL survival. Moderate knockdown of BAFF-R in MCL cells did not affect its viability, but sensitized them to cytarabine treatment in vitro and in vivo, with prolonged mice survival. Anti-BAFF-R antibody treatment promoted drug-induced MCL cell death. Conversely, the addition of recombinant BAFF (rhBAFF) to MCL cells protected them from cytarabine-induced apoptosis. We tested the efficacy of a humanized defucosylated ADCC optimized anti-BAFF-R antibody in killing MCL. Our data show both in vitro and in vivo efficacy of this antibody for MCL therapy. To conclude, our data indicate that BAFF/BAFF-R signaling is crucial for survival and involved in drug resistance of MCL. Targeting BAFF-R using BAFF-R antibody might be a promising therapeutical strategy to treat MCL patients resistant to chemotherapy.